Galatea : a short story - Miller, Madeline (Ecco, an imprint of HarperCollinsPublishers, 2022)
"In ancient Greece, a skilled marble sculptor has been blessed by a goddess who has given his masterpiece--the most beautiful woman the town has ever seen--the gift of life. After marrying her, he expects Galatea to please him, to be obedience and humility personified. But she has desires of her own and yearns for independence. In a desperate bid by her obsessive husband to keep her under control, Galatea is locked away under the constant supervision of doctors and nurses. But with a daughter to rescue, she is determined to break free, whatever the cost..."--